2022
DOI: 10.26464/epp2022012
|View full text |Cite
|
Sign up to set email alerts
|

The 600 keV electron injections in the Earth’s outer radiation belt: A statistical study

Abstract: 1. 600 keV electron injections are observed at 4.5 < L < 6.4 under different geomagnetic conditions of 450 nT < AE < 1450 nT.2. Before the electron injections, the flux negative L shell gradient for ≤ 0.6 MeV electrons or the low electron fluxes in the injected region are observed.3. For 600 keV electron injections at different L shells, the source populations from the Earth's 1 plasma sheet are different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
0
7
0
1
Order By: Relevance
“…The fastest possible increase of F ( E , t ) is still like E 2 (with a = 0), corresponding to a null gradient of PSD, ∂f ( p )/ ∂p = 0. But this would require injections of high energy E > 500 keV electrons, which are usually too rare and much too weak at L < 6.5 (Tang et al., 2022 ) to reach such a null PSD gradient. In the outer radiation belt, electron fluxes are initially steeply decreasing toward higher energy before chorus‐driven energization occurs during storm recovery (Murphy et al., 2018 ).…”
Section: Analytical Steady‐state Electron Distribution and Flux Due T...mentioning
confidence: 99%
See 1 more Smart Citation
“…The fastest possible increase of F ( E , t ) is still like E 2 (with a = 0), corresponding to a null gradient of PSD, ∂f ( p )/ ∂p = 0. But this would require injections of high energy E > 500 keV electrons, which are usually too rare and much too weak at L < 6.5 (Tang et al., 2022 ) to reach such a null PSD gradient. In the outer radiation belt, electron fluxes are initially steeply decreasing toward higher energy before chorus‐driven energization occurs during storm recovery (Murphy et al., 2018 ).…”
Section: Analytical Steady‐state Electron Distribution and Flux Due T...mentioning
confidence: 99%
“…In the Earth's outer radiation belt, the great variability of low‐energy (∼10–300 keV) electron injections and betatron acceleration during dipolarization events (Birn et al., 1998 , 2012 , 2014 ; Gkioulidou et al., 2015 ; Liu et al., 2016 ; Runov et al., 2015 ; Su et al., 2014 ; Tang et al., 2022 ; Turner et al., 2015 , 2016 ), and of the plasma and geomagnetic field conditions determining their subsequent acceleration to higher energy (O. V. Agapitov et al., 2019 ; Birn et al., 1997 ; Horne et al., 2005 ; Summers et al., 1998 ), are important obstacles to reliable predictions of full relativistic electron flux energy spectra during highly disturbed periods.…”
Section: Introductionmentioning
confidence: 99%
“…Several other mechanisms can explain rapid enhancements of relativistic electrons in the Earth's outer radiation belt. Previous observations and simulations have shown that relativistic electron injections could lead to rapid enhancements of MeV electrons in the outer radiation belt, which were associated with the intense substorm electric fields or convection electric fields (e.g., Ganushkina et al., 2013; Ingraham et al., 2001; Kim et al., 2000; X. Li et al., 1998; Mithaiwala & Horton, 2005; Tang et al., 2022; Xiong et al., 2022). In addition, an interplanetary (IP) shock acceleration is also an important mechanism, which is caused by IP shock compressions on the dayside (e.g., Blake et al., 1992; Foster et al., 2015; Hudson et al., 2017; Kanekal et al., 2016; Schiller et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Noted that there were some small increases in the blue/black lines, which were caused by the local magnetic field increases or substorm electron injections (e.g., Tang, Zhang, et al, 2016;C. L. Tang et al, 2018C. L. Tang et al, , 2022.…”
Section: Data and Statistical Methodsmentioning
confidence: 99%
“…Some studies have also shown that substorm electron injections or enhanced convection can directly explain the rapid enhancements of relativistic electrons in the outer radiation belt (e.g., Dai et al., 2014, 2015; Ganushkina et al., 2013; H.‐J. Kim et al., 2021; X. Li et al., 1998; Su et al., 2014; Tang, Zhang, et al., 2016; Tang et al., 2022; S. Xiong et al., 2022).…”
Section: Introductionmentioning
confidence: 99%